Diagnostic and prognostic value of plasma level of microRNA-92a in acute myeloid leukemia - El-Halawani, Nabil; Hamed, Nahla; Eldafrawi, Mohamed; Mourad, Zeinab; Sorour, Amani; Ghallab, Omar (Scientific Research Publishing, 2014)
Background: MicroRNAs (miRNAs) are short noncoding RNAs of ~21 to 23 nucleotides in length that post-transcriptionally regulate mRNA expression. Highthroughput methodologies have shown deregulated miRNA expression in an increasing number of human cancers. MiRNA expression patterns have been found to distinguish tumors of different developmental origin, even better than traditional mRNA expression profiling. Aim: To assess the plasma level of microRNA-92a in adult acute myeloid leukemia and to correlate it with prognostic factors and therapeutic response. Patients and Methods: This study was carried out on fifty AML patients as well as fifty healthy subjects as control. Conventional cytogenetics was performed on patients group only while measurement of the plasma level of miRNA-92a using TaqMan quantitative RT-PCR with miRNA-638 as endogenous reference for standardization and FLT3/ITD mutation was performed on patients and controls. Results: The differences in the ratio or relative quantitation (RQ) of plasma miRNa-92a to miRNA-638 in patients group to the control group have confirmed statistical significance. Also there was significant negative correlation between RQ of miRNA-92a and white blood count in patient group. Patients who achieved a response after induction chemotherapy had a mean RQ of miRNA-92a higher than non-responder with statistical significance. With regard to cytogenetics, favorable risk cytogenetics had meant RQ of miRNA-92a that was comparable to intermediate risk cytogenetics. While poor risk cytogenetics had a mean RQ which is significantly lower than both favorable and intermediate risk cytogenetics. Summary/Conclusions: Our data suggest the potential importance of the microRNA-92a as noninvasive cancer biomarkers helping in diagnosis, clinical prediction and therapeutic response.
Keywords: Acute Myeloid Leukemia; miRNAs; miRNA-92a; miRNA-638; Biomarker